The psychosocial effects of the anglophone conflict on civilians in Bamenda, Cameroon (African Journal of Law and Politics, 2025)
The Anglophone conflict in Cameroon has attracted a lot of attention from researchers since it escalated in 2017. Most of the studies have detailed the noticeable effects of the violent nature of this conflict, such as the numbers killed, raped and displaced, the number of villages razed and the material damage to infrastructure. While most of the studies focus on the physical effects, the psychosocial effects of the conflict have been ignored in the literature. This paper aims at filling this gap by assessing the psychosocial effects of the violent nature of the Anglophone conflict in Cameroon on civilians in Bamenda town. It adopts a qualitative approach in which 20 respondents from Bamenda in the Northwest region of Cameroon were interviewed. They were drawn from a range of backgrounds to learn more about the psychosocial effects of the violence. It was discovered that violence, either from its perpetrator or victim, does not only leave marks on the human body but also on the mind, the spirit and the social structure. Hence, ‘after violence’ could become ‘before violence,’ if the psychosocial effects of the violence from the Anglophone conflict are not dealt with properly.